2021
DOI: 10.2147/prbm.s341685
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Team Expertise Location Awareness in Improving Team Improvisation: A Dynamic Knowledge Integration Perspective

Abstract: Purpose The uncertainties in the market have led to an increasing number of uncertainties and unexpected situations in the work environment of organizations. Based on information processing theory, we investigate how teams can dynamically integrate the expertise of their members to better respond to an uncertain market environment. We propose an important team cognition: team expertise location awareness and point out its unique impact on knowledge integration and thus on improvisation capabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Finally, correlation analysis and regression analysis are obtained. The calculations involved in reliability analysis and validity analysis are shown in Eqs 1–3 ( Ye and Chen, 2021 ).…”
Section: The Influence Of Psychological Capital Combined With Ideolog...mentioning
confidence: 99%
“…Finally, correlation analysis and regression analysis are obtained. The calculations involved in reliability analysis and validity analysis are shown in Eqs 1–3 ( Ye and Chen, 2021 ).…”
Section: The Influence Of Psychological Capital Combined With Ideolog...mentioning
confidence: 99%
“…on comprehensiveness (Ye and Chen, 2021). It is not a simple combination of management disciplines such as marketing, human resources, finance, and quality control but a complete system built around the entire life cycle of a company.…”
Section: Approaches To Innovation and Entrepreneurship Education In A...mentioning
confidence: 99%
“…It was also an effective tool for cultivating self-confidence, especially for the disabled. According to the European Association for DMT , DMT filled the gap between the advantages of dance and the difficulties of sports activities by combining expressive exercise and creativity ( Khan, 2020 ; Ye and Chen, 2021 ). Dryman and Heimberg (2018) revealed that proficient emotion regulators developed fewer depressive symptoms.…”
Section: Related Workmentioning
confidence: 99%